Heat Conduction Third Edition - Jiji, Latif M. (Springer Berlin Heidelberg, 2009)
This textbook presents the classical topics of conduction heat transfer and extends the coverage to include chapters on perturbation methods, heat transfer in living tissue, and microscale conduction. This makes the book unique among the many published textbook on conduction heat transfer. Other noteworthy features of the book are: The material is organized to provide students with the tools to model, analyze and solve a wide range of engineering applications involving conduction heat transfer. Mathematical techniques are presented in a clear and simplified fashion to be used as instruments in obtaining solutions. The simplicity of one-dimensional conduction is used to drill students in the role of boundary conditions and to explore a variety of physical conditions that are of practical interest. Examples are carefully selected to illustrate the application of principles and the construction of solutions. Students are trained to follow a systematic problem solving methodology with emphasis on thought process, logic, reasoning and verification. Solutions to all examples and end-of-chapter problems follow an orderly problems solving approach. Extensive training material is available on the web A solution manualfor teachers is available on request